Adaptation of the Kessler Psychological Distress Scale (K10) for Argentinean population - Brenlla, Maria Elena (2010)
The aim of this study was to adapt the Kessler Psychological Distress Scale (K10) for Argentinean population. We conducted a linguistic adaptation of the instrument and an analysis of its psychometric properties. To assess the reliability of the scale, analysis of internal consis- tency was made through Cronbach’s alpha and temporal stability of the items was examined in two different subsamples. In addition, the scale’s validity was assessed, taking into account convergent validity, criterion validity by contrasting groups and factorial composition of the K10. Receiver Operating Characteristic (ROC) analysis was carried out to assess sensitivity, specificity and the area under the curve (AUC). The results of the present study indicate that the K10 is an adequate instrument presenting strong psychometric properties for screeningpsychological distress in our environment.